THE ROLE OF PHRASEOLOGICAL UNITS IN OUR SPEECH - Asliddinov, Tohirbek (Журнал иностранных языков и лингвистики, 2021)
The article focuses on the importance of learning the phraseological layer of a language, being learned. The author identifies and depicts the definition of a “phraseological unit” given by outstanding scientists. Examples of phenomena are given in the article. The author of the article also introduces some effective ways of enriching learners’ vocabulary base.